Upaya Adaptasi Struktural Untuk Mengurangi Risiko Dan Dampak Banjir Di Kawasan Rawan Bencana Banjir Kelurahan Damai Bahagia Kota Balikpapan - Cahyani, Anggi Dwi; Kadri, Mohtana Kharisma; Ariyaningsih; Mustofa , Umar (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
In 2022, the city of Balikpapan experienced 32 flood disasters spread across all sub-districts in Balikpapan City (BPS, 2023). The subdistrict that experienced the most flood disasters was South Balikpapan Subdistrict, where in this subdistrict there were 36 floods from 2020 to 2021. In this subdistrict, the subdistrict with a flood disaster in 2022 was Damai Bahagia Subdistrict. There have been efforts made by the government to deal with flooding, but this has not completely overcome the risk of flooding that occurs. For this reason, further research is needed in formulating effective structural adaptation efforts to reduce the risk and impact of flood disasters in Damai Bahagia Village. In this research, data collection was carried out using primary and secondary surveys, while the analysis method was carried out using content analysis and triangulation. From the results of the analysis, the factors that cause flooding and the structural adaptation efforts that have been carried out to deal with the flood disaster that occurred in Damai Bahagia Village were obtained. Then these results are used to formulate structural adaptation efforts to reduce the impact and risk of flood disasters in flood-prone areas of Damai Bahagia Village.